Humidity-dependent wound sealing in succulent leaves of Delosperma cooperi – An adaptation to seasonal drought stress - Speck, Olga; Schlechtendahl, Mark; Borm, Florian; Kampowski, Tim; Speck, Thomas (Beilstein Journal of Nanotechnology, 2018)
During evolution, plants evolved various reactions to wounding. Fast wound sealing and subsequent healing represent a selective advantage of particular importance for plants growing in arid habitats. An effective self-sealing function by internal deformation has been found in the succulent leaves of Delosperma cooperi. After a transversal incision, the entire leaf bends until the wound is closed. Our results indicate that the underlying sealing principle is a combination of hydraulic shrinking and swelling as the main driving forces and growth-induced mechanical pre-stresses in the tissues. Hydraulic effects were measured in terms of the relative bending angle over 55 minutes under various humidity conditions. The higher the relative air humidity, the lower the bending angle. Negative bending angles were found when a droplet of liquid water was applied to the wound. The statistical analysis revealed highly significant differences of the single main effects such as “humidity conditions in the wound region” and “time after wounding” and their interaction effect. The centripetal arrangement of five tissue layers with various thicknesses and significantly different mechanical properties might play an additional role with regard to mechanically driven effects. Injury disturbs the mechanical equilibrium, with pre-stresses leading to internal deformation until a new equilibrium is reached. In the context of self-sealing by internal deformation, the highly flexible wide-band tracheids, which form a net of vascular bundles, are regarded as paedomorphic tracheids, which are specialised to prevent cell collapse under drought stress and allow for building growth-induced mechanical pre-stresses.
Keywords: hydraulics; mechanical pre-stress; paedomorphosis; self-sealing; wide band tracheids